TMJ Vibrations in Asymptomatic Patients Using Old and New Complete Dentures - Goiato, Marcelo Coelho [UNESP]; Garcia, Alicio Rosalino [UNESP]; Santos, Daniela Micheline dos [UNESP]; Pesqueira, Aldieris Alves [UNESP] (Wiley-Blackwell, 2010)
Purpose: The aim of this study was to assess the presence of temporomandibular joint (TMJ) noises in subjects with severe bone resorption, who have worn the same complete dentures for over 10 years, and 5 months after treatment with increments of acrylic resin on the occlusal surface after having new dentures in place.Methods: After applying the research diagnostic criteria (RDC)/temporomandibular disorder (TMD) questionnaire, 20 asymptomatic subjects were assessed before and 5 months after the new dentures were put in place. Joint vibrations were assessed by the Sono Pak program by selecting the vibrations that occurred during the opening and closing cycle.Results: The means of the results revealed a nonnormal distribution and were submitted to Kruskal-Wallis statistical analysis (p < 0.05). The vibration means were of low intensity (<= 9.96 Hz). After rehabilitation, there was a reduction in the vibrations (<= 5.2 Hz) statistically significant only at the end of mouth opening with the old dentures when compared with the other cycles.Conclusion: The intensity and number of occurrences of joint vibrations were reduced after 5 months of wearing new dentures.
Keywords: TMJ; vibration; complete denture